Childhood stress: neurobiology and association with adult physical and mental disorders (2011)
Many people experience significant stressful or traumatic events in childhood. These events often leave a scar that may manifest in the form of adult psychopathology and chronic physical conditions. The neurobiological basis of the link between these childhood experiences and adult health problems is increasingly being studied and understood. The advantage of this understanding is that even if the exposure to traumatic and stressful events in childhood cannot be entirely prevented, the consequences of such exposure may be ameliorated by the institution of early intervention to persons at greatest risk.